Szepcząc do uszu władców, czyli o roli eksperymentów we współczesnej ekonomii - Jakubowski, Rafał M.; Kuśmierczyk, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper gives a short outline of experimental economics, as branch of economics became very popular in the last years. It starts with the history of experiments in economics and moves on to describe their most important functions in the scientific studies. The main fields of interests are described, as well as the most significant results obtained thanks to the experiments. The paper also analyzes the methodology of the experiments, pointing out their strong and the weak sides. The paper ends up with summary which explains the growing interest in experiments observable in presen economics and with predications about their role in shaping the theory of economics. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 121-136